2021
DOI: 10.1053/j.ajkd.2020.11.015
|View full text |Cite|
|
Sign up to set email alerts
|

A Text Messaging Intervention for Dietary Behaviors for People Receiving Maintenance Hemodialysis: A Feasibility Study of KIDNEYTEXT

Abstract: Rationale and Objective: An important component of hemodialysis management involves delivery of complex dietary recommendations. The aim of this study was to determine the feasibility of a mobile phone text message intervention to improve dietary behavior in people on hemodialysis. Study design: Six-month randomized feasibility study. Setting and participants: Patients receiving maintenance hemodialysis across two health districts in Sydney, Australia. Interventions: Participants randomized to the intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 33 publications
(42 reference statements)
0
52
0
1
Order By: Relevance
“…Participants enrolled in the intervention arm of a randomised controlled trial, KIDNEYTEXT 14 were eligible for this sub-study. The study protocol for this trial has been published in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants enrolled in the intervention arm of a randomised controlled trial, KIDNEYTEXT 14 were eligible for this sub-study. The study protocol for this trial has been published in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…13 Feasibility and impact of a mobile phone text messaging intervention (KIDNEYTEXT) to change dietary behaviours in haemodialysis patients have been reported. 14 Feasibility and impact were assessed using recruitment and retention rates and change to the intake of renal-specific nutrients (potassium, phosphorus, sodium and protein). Evaluation of participants' experiences with KIDNEYTEXT is an important step to understand how the participants engaged with the intervention and to the extent it impacted on their dietary behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…31 Further limitations of the KIDNEYTEXT trial have been outlined elsewhere. 13 This simple mobile phone text message intervention may be adopted as an additional tool for patient care. There may be a cost saving for dialysis units in using text messages, in addition to individualised dietary counselling.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcomes of this text message based intervention on dietary behaviours have been published previously. 13 Here, we present the results of the trial-based economic evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…This was the only included study to report on the patient experience of the intervention. Our search identified a protocol for a study (KIDNEYTEXT), 37 which has subsequently published feasibility results in January 2021 38 . KIDNEYTEXT included three text messages per week (in addition to standard care) designed to improve dietary behaviours, and demonstrated that this type of intervention was feasible and acceptable to people on maintenance haemodialysis.…”
Section: Discussionmentioning
confidence: 99%